Pemuridan Relasional Bagi Kedewasaan Rohani Jemaat Gereja - Marlin, John (STT KINGDOM BALI, 2024)
Spiritual maturity is related to discipleship, one form of discipleship is relational discipleship. This research aims to describe relational discipleship and spiritual maturity. This study uses a qualitative method. The research results show that relational discipleship has a positive correlation with spiritual maturity, where the higher the implementation of relational discipleship, the higher the level of spiritual maturity..